Business-government relations and national economic models: A review and future research directions in varieties of capitalism and beyond. Issue 8 (17th November 2021) - MacKenzie, Niall G.; Perchard, Andrew; Miller, Christopher; Forbes, Neil
Abstract: This special issue complements and extends existing work in business history to show how the discipline can contribute to the Varieties of Capitalism (VoC) literature. The work in this collection delves deeper into our understanding of how VoC emerge and continue through the prism of business-government relations as the two principal actors in capitalist development. The focus of much of the existing canon on varieties of capitalism is centred on aggregated models of institutional environments. We take the cue from emerging work on the state and business in business history then to consider what this means for VoC, and to what end. In doing so, this collection bridges a number of different literatures, including those in business and economic history, economics, development studies, political economy and political science, to consider how 'varieties of capitalism' (VoC) shape, and are structured by, government-business relations over time.